2022
DOI: 10.3389/fpls.2022.890780
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping and Functional Research of Key Genes for Photoperiod Sensitivity in Maize

Abstract: Maize is native to the tropics and is very sensitive to photoperiod. Planting in temperate regions with increased hours of daylight always leads to late flowering, sterility, leggy plants, and increased numbers of maize leaves. This phenomenon severely affects the utilization of tropical maize germplasm resources. The sensitivity to photoperiod is mainly reflected in differences in plant height (PH), ear height (EH), total leaf number (LN), leaf number under ear (LE), silking stage (SS), and anthesis stage (AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Besides the number of lines, a major difference between previous studies and the results presented here is that morphological traits were not included when determining phylogenetic relationships and population structure. All traits are composed of genotypic and environmental effects, and many of the vegetative and phenological traits included in previous analyses of popcorn are known to be affected by photoperiod sensitivity, including plant height, ear height, leaf number, and days to flowering (Fei et al 2022). As few as four genomic regions have been identified that control photoperiod responses in these traits (Coles et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the number of lines, a major difference between previous studies and the results presented here is that morphological traits were not included when determining phylogenetic relationships and population structure. All traits are composed of genotypic and environmental effects, and many of the vegetative and phenological traits included in previous analyses of popcorn are known to be affected by photoperiod sensitivity, including plant height, ear height, leaf number, and days to flowering (Fei et al 2022). As few as four genomic regions have been identified that control photoperiod responses in these traits (Coles et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the number of accessions, a major difference between previous studies of North American Popcorn germplasm and the results presented here is that morphological traits were not included when determining phylogenetic relationships and population structure. All traits are composed of genotypic and environmental effects, and many of the vegetative and phenological traits included in previous analyses of popcorn are known to be affected by photoperiod sensitivity, including plant height, ear height, leaf number, and days to flowering (Fei et al., 2022). As few as four genomic regions have been identified that control photoperiod responses in these traits (Coles et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zm00001d005347 encodes monodehydroascorbate reductase homolog 1 (https://www.uniprot.org/ (accessed on 1 May 2023)). Many related reports have stated that this region is associated with several QTNs of essential traits, e.g., PH, EH, anthesis stage and seed desiccation [37,38]. The pedigrees of QB512 and QR273 include tropical materials, which have good resistance to MWS, but frustratingly, have long growth periods and poor seed desiccation.…”
Section: Transmission Of the Ibd Segmentsmentioning
confidence: 99%